The finding of Y-STR microdeletion involving DYS448, DYS392, DYS549 and DYS385a/b markers in a paternity case with deceased alleged father. (December 2015) - Beltramo, J.; Pena, M.A.; Lojo, M.M.
Abstract: In the context of a post mortem paternity case with the alleged grandfather as the only available reference sample, an acceptable LR value was reached (363830) by means of 20 autosomal markers (PowerPlex21 System). The child's YFiler haplotype showed a signal loss affecting markers DYS385a/b, DYS392 and DYS448. This finding was confirmed with the PPY23 marker set, where the loss of signal was also observed in DYS549 locus. The missing alleles map to the long arm of the Y chromosome, which encompass the AZFb + c deletion region. Since the grandfather's haplotype showed a complete profile, it could be assumed that the observed microdeletion is a de novo event which could have been occurred during grandfather's or father's meiosis. In addition, an inconsistency between Grandfather/child profile was also observed in the DYS481 marker, which could be explained by assuming a meiosis mutation (23 to 24).